The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1029/92jd02211
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol in the arid southwestern United States: Measurements of mass loading, volatility, size distribution, absorption characteristics, black carbon content, and vertical structure to 7 km above sea level

Abstract: Near-surface and lower tropospheric aerosol characteristics have been determined at several remote sites near Orogrande, New Mexico, using a variety of methods and sensors including quartz fiber filter samplers, hi-vol samplers, ground-based and aircraft-mounted light-scattering aerosol counters, an aerosol counter equipped with a heated inlet, and an aethalometer (a device that measures aerosol absorption). The results of these measurements, which have been taken sporadically over the last 15 years but with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 48 publications
5
39
0
Order By: Relevance
“…Bimodal size distributions adequately describe observed SWYVIS size distributions, and display slight broadening of the coarse mode with increasing altitude. In the accumulation mode, median particle diameters and geometric standard deviations (Tables 4 and 5) are very similar to those reported by Kim et al (1993a) and Pinnick et al (1993). For the coarse mode, however, both inter-and intrastudy comparisons of the diameters show slightly more variability, though modal standard deviations are comparable.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Bimodal size distributions adequately describe observed SWYVIS size distributions, and display slight broadening of the coarse mode with increasing altitude. In the accumulation mode, median particle diameters and geometric standard deviations (Tables 4 and 5) are very similar to those reported by Kim et al (1993a) and Pinnick et al (1993). For the coarse mode, however, both inter-and intrastudy comparisons of the diameters show slightly more variability, though modal standard deviations are comparable.…”
Section: Discussionsupporting
confidence: 67%
“…Examples in the marine environment include NARE-96 (Cowling et al, 1998), ACE-1 (Bates et al, 1998), ACE-2 (Collins et al, 2000a;, and INDOEX (de Reuss et al, 2001). Over coastal and continental locations, following earlier work of Rosen et al (1992), Kim et al (1993a), Gunter et al (1993), Pinnick et al (1993) and Gunter (1994), more elaborate airborne data sets have been acquired in the Arctic (Hegg et al, 1996), in the US mid-Atlantic coastal region (Hegg et al, 1997;Hartley et al, 2000), and over the Los Angeles Basin (Collins et al, 2000b), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ch)•lek and Hallet, 1992] that when soot is near the surfaces of droplets, its absorption may be enhanced. Calculations [Pinnick et al, 1993;Fuller, 1995a, b] have shown that this is certainly the case for soot located at selected positions on or in a droplet, with enhancements factors as high as about 20, but these same calculations also show locations where the refractive properties of the droplets actually shield the soot from incident light. Averages of absorption over positions near the surface of a host droplet [Fuller, 1995b] indicate that for txm-sized water droplets, there is very little net enhancement as long as the absorber's position is (as one would expect) unrestricted.…”
Section: Absorption By Soot Primaries Attached To Sulfate Particle Sumentioning
confidence: 99%
“…The proportion of small particles (< 10 µm) for most activities was less than 10% and generally was lower for dustier activities. Another study of natural aerosols in the arid southwestern United States concluded that near-surface aerosol is comprised to two modes: a wind-derived supermicron component which is likely soil-derived and local in origin and a submicron component that is likely a product of long-range atmospheric transport (Pinnick et al 1993 [160312] [160312]), the airborne particles originating from the local soils range in size from about 0.1 µm to about 100 µm.…”
Section: Particle Size Distribution Of Environmental Aerosolsmentioning
confidence: 99%